The empty raincoat : making sense of the future - Handy, Charles B. (Charles Brian), 1932- (London : Hutchinson, 1994)
In the dark wood. Finding the balance. Practising the preaching. The search for meaning.
Keywords: Work; Social prediction; Forecasting; Social prediction; Work -- Forecasting